Interventions connecting young people living in Africa to healthcare; a systematic review using the RE-AIM framework - Gbaja-Biamila, Titilola Abike; Obiezu-Umeh, Chisom; Nwaozuru, Ucheoma; Oladele, David; Engelhart, Alexis; Shato, Thembekile; Mason, Stacey; Carter, Victoria; Iwelunmor-Ezepue, Juliet (Frontiers in Health Services, 2024)
Introduction Africa's young people are among the least focused groups in healthcare linkage. The disproportionally high burden of youth-related health problems is a burden, especially in developing regions like Africa, which have a high population of young people. More information is needed about factors that impact linkages in healthcare and the sustainability of health interventions among young people in Africa. Methods A systematic literature search was performed from October 2020 to May 2022 in PubMed, CINAHL, Scopus, Global Health, and the Web of Science. Studies included in the review were conducted among young people aged 10–24 living in Africa, written in English, and published between 2011 and 2021. Results were reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Data was analyzed using narrative synthesis, synthesizing the details of the RE-AIM reporting component. Interventions were systematically compared using the Cochrane Collaboration risk-of-bias tool to evaluate the rigor of each intervention. Results A total of 2,383 potentially relevant citations were obtained after an initial database search. Retained in the final group were seventeen articles from electronic data searches; among these articles, 16 interventions were identified. Out of the seventeen studies, nine (53%) were randomized controlled trials, three (18%) were quasi-experimental designs, and five (29%) were observational studies. At the same time, the included interventions were reported on 20 (76.92%) of the 26 components of the RE-AIM dimensions. In eastern Africa, twelve (80%) interventions were conducted, and all the interventions addressed linkage to care for young people in preventing and treating HIV. The least reported RE-AIM dimensions were implementing and maintaining interventions connecting young people to care. Discussion Timely care remains critical to treating and preventing ailments. This review indicates that interventions created to link young people to care, especially HIV care, can help link them to health care and strengthen the programs. It is also clear that further research with more extended follow-up periods is needed to examine connections to care in all other aspects of health and to bridge the gap between research and practice in the care of young people in Africa. Systematic Review Registration PROSPERO [CRD42022288227].